Current state of off the shelf scaffolds and implants for meniscal replacement - Claudia Ghisa; Kenneth R. Zaslav (Elsevier, 2022)
Partial meniscectomy has been a mainstay of treatment for mechanical symptoms of meniscal tear for decades. Yet, clear changes in load distribution have been reported after loss of meniscal integrity and degenerative changes have been seen after these procedures over time. While meniscal repair is preferred whenever possible, these repairs are not always possible or successful. In recent years options have been developed to try to mitigate these post meniscectomy symptoms and sequelae, including off-the-shelf scaffolds and implants for meniscal replacement. Although not widely adopted in the United States yet, these implants have been used in Europe more extensively and now have been through multiple prospective and randomized controlled studies. We report an update on this literature here and the regulatory status of these implants for the readers of JCJP.